Simulation Analysis of PMD and Dispersion Mapping Techniques - Singh, Hardeesh (My University, 2008)
Optical fibers are not only used in the telecommunication but also used in the Internet and Local Area Networks (LAN) to achieve high signalling rates. Optical networks, based on the emergence of the optical layer in transport networks, provide higher capacity and reduced costs for new applications such as the Internet, video and multimedia interaction, and advanced digital services. But the linear and nonlinear characteristics of the fiber optical are the limiting factors to reach the goals. The objective of the thesis work is to investigate the limiting factors of the guided optical media. In the standard single mode fibers, the Polarization Mode Dispersion is the phenomenon that causes the hurdles to reach the high bit-rate-distance product of amplified lightwave communication system. The impacts on eye opening, eye closing and output power due to PMD variation are studied. The impacts of PMD, in high data rate transmission systems have been investigated at different bit rates. It is reported that PMD produces the adverse effect on the eye opening, eye closing, and power at the output. Due to PMD, the significant degradation in the performance of high speed optical transmission system with the increasing bit rate is also reported. At the bit rate of 40 Gbps and above it is almost impossible to cope with PMD without the use of dispersion compensation. The fiber nonlinear characteristics are the Optical Kerr effect and the stimulated scatterings. The fiber nonlinearities produce the input power limitations on the system as well as maximum transmission distance. To mitigate their effects, the dispersion mappings are used. Pre, post and hybrid or symmetrical compensation techniques are compared on the basis of bit error rate (BER) variation with the input power at higher bit rates. The dispersion compensation fiber (DCF) is used in the compensation techniques. It is demonstrated that the hybrid compensation is better to reduce the nonlinear effects than its counterparts. The increase in BER due to increase in the input power for all the three techniques is also reported. Simulation results are presented to support the analysis PMD impacts and the comparison of compensation techniques.
M.E. (ECED)
Keywords: PMD, Dispersion, BER; Mapping